The talk scandal as mediatized event and communicative resource in far-right populist talk. (June 2019) - Patrona, Marianna
Abstract: This paper examines the discursive realizations and media representations of scandalous talk with reference to a scandalous 2018 parliamentary speech performance by a representative of the far-right Golden Dawn (GD) party in Greece. By examining the recontextualization of the talk scandal in on-line news articles, it is shown that the original speech event gives rise to other speech events related to it, creating a 'talk scandal universe'. Viewing talk scandals as building blocks upon which engaging media narratives are built, it is argued that they can serve as communicative resources in far-right populist performances, enacting a clean break with established norms and values of the political establishment. Moreover, talk scandals project perpetrators as candid, outspoken and defiant of the status quo, even in the face of damaging face or suffering legal penalties. Finally, as scandalous utterances and subsequent retractions contain political positioning statements, talk scandals in effect help spread and reproduce populist agendas.